Knowledge and skills of entry-level accountants in Afghanistan : perceptions of practitioners and academicians - Azimi, Elham
Human capital theory suggests that education is an efficient tool for the development of the workforce by improving the competencies required to fulfil a specific economic endeavour (Becker, 1993). This is why accounting education has been continuously criticised for failing to equip graduates with the important knowledge and skills needed in the workplace (Albrecht & Sack, 2000). Employers report that entry-level accountants do not possess the required knowledge and skills when entering the workforce (Low et al., 2013; Altarawneh, 2016); and a gap exists between the knowledge and skills required in the workplace and the knowledge and skills graduates acquired from their university education (Abayadeera & Watty, 2014; Botes & Sharma, 2017). This study explores the perceptions of accounting practitioners and educators on the knowledge and skills required for entry-level accountants in Afghanistan; it also examines the knowledge and skills they have acquired through university education. This study adopts quantitative method by way of questionnaire-based survey to analyse the data collected from 92 practitioners and 83 educators in Afghanistan. It was found that there is no significant difference in the perceptions of the respondents regarding the required knowledge and skills of entry-level accountants. Generally, respondents perceived all of the knowledge and skills components to be either very important or important for entry-level accountants. In particular, the knowledge items perceived most important are 'preparing and analysing financial statements, understanding double-entry system and bookkeeping of financial transactions, understanding standards of financial reporting, financial management, understanding basic cost and management accounting, and taxes.' Similarly, the skills perceived most important are 'the use of accounting software, manage time properly, leadership skills, present and defend points of view in writing, basic computer skills, professional behaviour, ethics and social responsibility, and key accounting skills/ numeracy skills.' Regarding the competence level of entry-level accountants, results show that graduates only possess just a minimum level of the required knowledge and skills, and they are not adequately competent. Interestingly, both accounting practitioners and educators perceived that a gap exists between the required knowledge and skills in practice and acquired knowledge and skills by graduates. The findings of this study further suggest that the gap that exists is even larger for understanding standards of financial reporting, and accounting software skills. Overall, this study will be beneficial for both academicians and practitioners in Afghanistan as it highlights the types of knowledge and skills that the entry-level accountants should be exposed to, and the gaps between the required and acquired accounting competencies. The Afghanistan Ministry of Higher Education could take effective steps in bridging these gaps by incorporating essential courses, such as introduction to financial reporting standards (e.g. IFRS), accounting software into university curriculums, and similar others.